Safety and efficacy of Labisia pumila containing products - Muhammad Syafiq Saleh; Shazwani Shaharuddin; Md Moklesur Rahman Sarker; Long Chiau Ming (Archives of Global Professionals, 2016)
Labisia pumila is a traditional medicinal plant which has wide therapeutic application including induction of labor and treatment of dysentery, dysmenorrhea and gonorrhea. We aimed for systematic review of the efficacy andsafety of L. pumila extract or its other commercial products availabe in Malaysian market. The marketed 500 mg capsule is composed of 40 mg L. pumila, 10 mg C. caudatum extract and 450 mg excipient. The commercial products did not follow the registration guidelines of Malaysian National Pharmaceutical Control Bureau (NPCB) and advertisement guidelines of Malaysian Advertisement Board. Randomized, placebo controlled clinical trials reported the safe consumpotion of L. pumila water extract on postmanoposal women. Information on the efficacy and safety of commercial products are not sufficiently available. Many unregistered products (mostly capsule form) are flooded in Malaysian market without having scientific information. Consumption of those products may seriously impair the health of the people.